Comparison of metabolic alterations, hepatic and cardiovascular damage between primary NAFLD and HIV-associated NAFLD: Role of low visceral adiposity. (March 2023) - Lombardi, R.; Cinque, F.; Cespiati, A.; Marchesi, L.; Francione, P.; Fatta, E.; Bertelli, C.; Pisano, G.; Oberti, G.; Colavolpe, L.; Alletto, F.; Dongiovanni, P.; et al.
Abstract : People with HIV (PWH) are at risk of developing NAFLD due to frequent metabolic comorbidities, chronic HIV-related inflammation, and exposure to antiretroviral therapy. However, whether HIV-associated NAFLD differs in clinical presentation from primary NAFLD is still unknown. To compare metabolic, hepatic and cardiovascular (CV) alterations in PWH with hepatic steatosis (HS) and primary NAFLD patients. 30 consecutive HIV mono-infected patients (mean age 46+12 years, male 81%; 90% with viral suppression) with HS at ultrasound, in absence of alcohol abuse, were compared to 60 NAFLD patients matched for sex and age. For all subjects, anthropometric parameters, metabolic comorbidities, fat mass and sarcopenia by bioimpedance, liver damage by transaminases and Fibroscan (advanced fibrosis>F3 for LSM>8.9/7.2kPa M/XL probe), CV damage by carotid ultrasound (plaques, arterial stiffness by radiofrequency as pulse wave velocity) and heart ultrasound (systolic and diastolic function and epicardial adipose tissue - EAT) were assessed. PWH with HS presented lower BMI (27.1+4 vs 29.1+4.3 Kg/m 2, p=0.04), waist circumference (98+9 vs 103.1+10.3 cm, p=0.03) and trunk fat mass (9.8+3.3 vs 12.4+4.7 Kg, p=0.02) compared to primary NAFLD patients. Nevertheless, the prevalence of metabolic alterations (type 2 diabetes 13% vs 13%; hypertension 47% vs 42%; dyslipidemia 83% vs 85%) and sarcopenia (40% vs 52%) was similar among the two groups, with superimposable liver damage (increased transaminases 17% vs 20%; advanced fibrosis 17% vs 12%) and CV damage (high CV risk 84% vs 83%; carotid plaques 39% vs 28%; increased EAT 20% vs 17%; systolic dysfunction 6% vs 5%; diastolic dysfunction 7% vs 6%; pulse wave velocity values 7.4+2 vs 6.9+1.4 m/s). PWH with HIV-associated NAFLD have lower BMI and lower visceral adiposity compared to primary NAFLD patients despite similar prevalence of metabolic, liver and CV damage. Therefore, screening and follow up for HS in HIV patients is mandatory independently of their body weight.